2006
DOI: 10.1002/imhj.20085
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Architecture in Infants of Substance-Abusing Mothers

Abstract: Sleep Architecture in Infants of Substance Abusing MothersThis longitudinal, year-long study compared sleep-wake state organization in two groups of infants: infants whose mothers abused substances during their pregnancies, and non-exposed, typically developing, age-matched comparison infants, to determine whether differences in sleep-wake state organization existed between the two groups. Seventeen infants of mothers who were participating in a parent-infant residential treatment program for substance abuse w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“… found no differences in sleep–wakefulness patterns of 3‐month‐old infants exposed to opiates in utero , compared with control infants, and Hanft et al. , in a matched case control study of 17 infants of substance abusing mothers, reported no change in sleep state organization measured over several time points during the first year of life. Our findings support the notion proposed by these authors that sleep system regulators must be highly resilient and well organized to preserve the arousal responses of infants exposed to prenatal substance abuse.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… found no differences in sleep–wakefulness patterns of 3‐month‐old infants exposed to opiates in utero , compared with control infants, and Hanft et al. , in a matched case control study of 17 infants of substance abusing mothers, reported no change in sleep state organization measured over several time points during the first year of life. Our findings support the notion proposed by these authors that sleep system regulators must be highly resilient and well organized to preserve the arousal responses of infants exposed to prenatal substance abuse.…”
Section: Discussionmentioning
confidence: 93%
“…, in a matched case control study of 17 infants of substance abusing mothers, reported no change in sleep state organization measured over several time points during the first year of life. Our findings support the notion proposed by these authors that sleep system regulators must be highly resilient and well organized to preserve the arousal responses of infants exposed to prenatal substance abuse. These authors also include sleep architecture into that notion of protection, but our study was too short and fragmented to study this aspect.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies suggest that sleep fragmentation (i.e., sleep disruption due to arousals or awakening), as opposed to sleep-wake state organization (i.e., the proportion and sequencing of sleep stages), may be a better indicator of prenatal substance exposure. Hanft et al (2006) demonstrated that infants of substance-abusing mothers, compared to non-exposed controls, spent less total time asleep, and their longest sleep period was significantly shorter. However, the groups did not differ in the proportion of other sleep-wake variables (i.e., active sleep %, quiet sleep %, awake %, number of nighttime awakenings), suggesting that in utero exposure to substances may not always affect overarching organization and proportion of sleep-wake states.…”
Section: Alcohol Circadian Rhythms and Sleepmentioning
confidence: 96%
“…close contact; AA ϭ arousing activities; Nurs ϭ nursing; Bott ϭ bottle-feeding; Dist ϭ infant distress; Asl ϭ infant sleep. The amount of time spent asleep at each age point is comparable to other studies using video-somnography (e.g.,Hanft, Burnham, Goodlin-Jones, & Anders, 2006).‫ء‬ p Ͻ .05. ‫ءء‬ p Ͻ .01.This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
mentioning
confidence: 99%